The effects of a financial transaction tax in an artificial financial market - Daniel Fricke; Thomas Lux (Kiel Institute for the World Economy (IfW), 2013)
We investigate the effects of a Financial Transaction Tax (FTT) in an order-driven artificial financial market. FTTs are meant to limit short-term speculative behavior by reducing the amount of excess liquidity in the system. To quantify these effects, adjustments in trading strategies and their effects on liquidity need to be taken into account. We model an agent-based continuous double-auction, allowing for a continuum of investment strategies within the chartist/fundamentalist framework. For certain parameter combinations, our model is able to reproduce certain stylized facts of financial time-series. We find largely positive effects of the FTT for small tax rates. Additionally, for large tax rates we find the effects not to be as negative as previously found.
Keywords: H20; C63; D44; 330; Transaction Tax; Tobin Tax; Market Microstructure; Agent-Based Models; Speculative Bubbles